Fundamentals of vehicle dynamics - Gillespie, T. D. (SAE International, 2021)
A world-recognized expert in the science of vehicle dynamics, Dr. Thomas Gillespie has created an ideal reference book that has been used by engineers for 30 years, ranging from an introduction to the subject at the university level to a common sight on the desks of engineers throughout the world. As with the original printing, Fundamentals of Vehicle Dynamics, Revised Edition, strives to find a middle ground by balancing the need to provide detailed conceptual explanations of the engineering principles involved in the dynamics of ground vehicles with equations and example problems that clearly and concisely demonstrate how to apply such principles. A study of this book will ensure that the reader comes away with a solid foundation and is prepared to discuss the subject in detail. Ideal as much for a first course in vehicle dynamics as it is a professional reference, Fundamentals of Vehicle Dynamics, Revised Edition, maintains the tradition of the original by being easy to read and while receiving updates throughout in the form of modernized graphics and improved readability. Inasmuch as the first edition proved to be so popular, the Revised Edition intends to carry on that tradition for a new generation of engineers.